Determination of predicted output for different heights of wind turbine location - Garanzha Igor; Golikov Alexander; Pisareva Milena (E3S Web of Conferences)
Today the world is experiencing a significant increase in the capacity of renewable energy sources. Current development forecasts tell us that renewable energy sources (RES) could account for up to 20% of the global energy mix by 2030 (excluding large-scale hydropower). But the forecasts will be realized if these energy sources are developed and introduced into the practice of producing electrical energy as quickly and widely as possible. It will take 30 to 50 years for new energy sources to increase their share of the total energy budget from 1% to 10%. In world practice, the use of wind turbines with a capacity of up to 1 MW is considered unpromising. Wind turbines with a capacity of up to 3 MW have received great development. In 2008, the first wind generators with a capacity of 6…8 MW were built in Europe. Investments in the development of Russian wind energy using new wind turbines from EVIAG AG, namely EV 90 and EV 100 are promising. It has been revealed that the total output over the service life of the facility constantly increases with height. However, taking into account the increase in one-time costs during the construction of the facility, the increase in the cost of its operation, we can conclude that the most acceptable tower height for the Turbowind T 600-48 will be within 50...60 m, and for the Eviag EV 100 - 90…100 m. Knowing that the cost of the construction part of wind energy complex facilities in most cases is approximately 10…40% of the cost of the wind turbine itself, and at the same time as calculations have shown an increase in costs associated with changing the height of the tower by 20% gives an increase in profit by 60%, you can quite profitably operate with the tower height parameter, taking the most rational.